Shorea robusta Bark Extract as a Novel Green Inhibitor for Mild Steel Corrosion in 1 M H2SO4 Solution - Bajgai, Ajay Kumar; Karki, Rajaram; Thapa Magar, Jamuna; Homagai, Puspa Lal; Oli, Hari Bhakta; Bhattarai, Deval Prasad (Amrit Research Journal, 2022)
Extract of Shorea robusta bark as a novel green inhibitor for mild steel (MS) corrosion has been investigated. Qualitative chemical tests, UV, and FTIR measurements were carried out to confirm phytochemicals in the extract. Gravimetric as well as electrochemical methods were employed to examine the inhibition efficiency of the extract. Effects of inhibitor concentration, immersion time as well as working temperature were investigated by weight loss measurement method. Weight loss measurement reveals the maximum inhibition efficiency of 1000 ppm inhibitor for half an hour immersion time. Also, 1000 ppm inhibitor can work up to a temperature of 55°C with 50% efficiency. Electrochemical measurements reflected the mixed type of inhibition behavior of the inhibitor. Polarization measurement results, the 93.73% and 75%, respectively for as-immersed and immersed samples in1000 ppm inhibitor concentration. Based on these findings, it is revealed that the Shorea robusta bark extract could be used as low temperature inhibitor.